Difficulties of Artistic Education Teaching In The Primary Schools in Baghdad (Journal of the College of Basic Education, 2019)
This study aims to identify the most important difficulties facing the teaching of art education from the point of view of its teachers and supervisors in Baghdad primary schools، and ways to address them. To achieve the objective of the study، the researcher used the descriptive analytical method. Of them (65) teachers، (15) supervisors. The study reached the following results: -The most difficulties faced by teachers in teaching art education are the difficulties related to the teacher، and then came the difficulties related to the physical and social side، the difficulties related to the curriculum، and the difficulties associated with the learner in the last place. The results also showed that there were no statistically significant differences at the level of significance (0.05%) in the responses of teachers of art education and their supervisors to the difficulties they face due to variables (gender، educational qualification، years of experience) The study concluded with a set of recommendations، the most important of which are holding seminars and workshops on increasing the awareness of school administration and teachers about the importance of art education and developing its programs.